Juridical Analysis of the Application of the Precautionary Principle in Business Contracts for the Utilization of Natural Resources in the Mining Sector - Devi Mutiara Sanni (Universitas Negeri Semarang, 2026)
The application of the precautionary principle in the management of natural resources constitutes an essential aspect in ensuring the achievement of sustainable development. This principle requires the adoption of preventive measures in every activity that has the potential to cause environmental damage. This research aims to analyze the application of the precautionary principle in business contracts within the mining sector and its implications for environmental protection and legal certainty. The research method employed is normative juridical, utilizing a statutory approach. Legal sources were obtained through the study of legislation, legal doctrines, and academic literature. The findings indicate that, in practice, mining business contracts in Indonesia remain primarily focused on commercial aspects and have not yet fully internalized the precautionary principle. This condition results in weak environmental protection and potential long-term socio-ecological losses. The study recommends the construction of contracts that incorporate the precautionary principle as a normative standard, so that contracts function not only as private agreements but also as preventive legal instruments to support environmental protection and sustainable development.